Differentially expressed gene transcripts in roots of resistant and susceptible chickpea plant (Cicer arietinum L.) upon Fusarium oxysporum infection - Nimbalkar, Suhas B.; Harsulkar, Abhay M.; Giri, Ashok P.; Sainani, Mohini N.; Franceschi, Vincent R.; Gupta, Vidya S. (Physiological and Molecular Plant Pathology, 2006)
Differentially expressed genes in chickpea, (Cicer arietinum L.) during root infection by Fusarium oxysportan f sp. ciceri Racel, were identified using cDNA-RAPD and cDNA-AFLP approaches. The former employed decamer primers on cDNA template and revealed nine differentially expressed transcripts in the resistant-infected chickpea variety. Among the 2000 transcript-derived fragments (TDFs) screened by cDNA-AFLP, 273 were differentially expressed in chickpea roots during Fusaritan infection. Only 13.65% of the TDFs were differentially regulated during pathogen challenge, while the other 86% were expressed non-differentially during the process of pathogen infection in chickpea roots. Nineteen TDFs, which expressed differentially in the resistant-infected chickpea variety were cloned and sequenced. Two of these TDFs were similar to transcription factors like WRKY proteins and 14-3-3 proteins, while three TDFs represented the NBS-LRR-type gene sequences. Two TDFs had sequence identity to genes known to have function in defense. The RAPID TDF CaFRi60 showed sequence identity to gamma-glutamyl-cysteine synthetase. Among the TDFs examined by cDNA-AFLP, 19 were confirmed by Reverse Northern blot to be differentially expressed. The data confirms the effectiveness of the cDNA-AFLP technique in detecting differentially expressed genes during pathogenesis. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: cDNA-AFLP; Chickpea; Cicer arietinum; differentially expressed genes; fusarium oxysporum; Transcriptome

Differential transcriptional activity of SAD, FAD2 and FAD3 desaturase genes in developing seeds of linseed contributes to varietal variation in alpha-linolenic acid content - Rajwade, Ashwini V.; Kadoo, Narendra Y.; Borikar, Sanjay P.; Harsulkar, Abhay M.; Ghorpade, Prakash B.; Gupta, Vidya S. (Phytochemistry, 2014)
Linseed or flax (Linum usitatissimum L.) varieties differ markedly in their seed a-linolenic acid (ALA) levels. Fatty acid desaturases play a key role in accumulating ALA in seed. We performed fatty acid (FA) profiling of various seed developmental stages of ten Indian linseed varieties including one mutant variety. Depending on their ALA contents, these varieties were grouped under high ALA and low ALA groups. Transcript profiling of six microsomal desaturase genes (SAD1, SAD2, FAD2, FAD2-2, FAD3A and FAD3B), which act sequentially in the fatty acid desaturation pathway, was performed using real-time PCR. We observed gene specific as well as temporal expression pattern for all the desaturases and their differential expression profiles corresponded well with the variation in FA accumulation in the two groups. Our study points to efficient conversion of intermediate FAs [stearic (SA), oleic (OA) and linoleic acids (LA)] to the final product, ALA, due to efficient action of all the desaturases in high ALA group. While in the low ALA group, even though the initial conversion up to OA was efficient, later conversions up to ALA seemed to be inefficient, leading to higher accumulation of OA and LA instead of ALA. We sequenced the six desaturase genes from the ten varieties and observed that variation in the amino acid (AA) sequences of desaturases was not responsible for differential ALA accumulation, except in the mutant variety TL23 with very low (<2%) ALA content. In TL23, a point mutation in the FAD3A gene resulted into a premature stop codon generating a truncated protein with 291 AA. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: ALA; Fatty acid desaturases; Fatty acids; Flax; Gene expression; Linseed

Dietary flaxseed oil and fish oil ameliorates renal oxidative stress, protein glycation, and inflammation in streptozotocin-nicotinamide-induced diabetic rats - Jangale, Nivedita M.; Devarshi, Prasad P.; Bansode, Sneha B.; Kulkarni, Mahesh J.; Harsulkar, Abhay M. (Journal of Physiology and Biochemistry, 2016)
Protective and prophylactic effects of omega-3 fatty acids on oxidative stress and inflammation are well known. We assessed beneficial effects of flaxseed oil and fish oil on streptozotocin (65 mg/kg; i.p.)-nicotinamide (110 mg/kg; i.p.) induced diabetic rats by studying renal expression of antioxidant and inflammatory genes. Diabetic rats given 10 % flaxseed oil or 10 % fish oil diet for 35 days showed significant decrease in renal lipid peroxidation. Flaxseed oil diet resulted in up-regulation of renal superoxide dismutase-1 (SOD-1) (activity and expression) and glutathione peroxidase-1 (GPx-1) expression. Furthermore, both diets up-regulated catalase (CAT) (activity and expression) and down-regulated heme oxygenase-1 (HO-1) expression. Both diets were able to limit the renal advanced glycation end products (AGEs) formation and reduced receptor of AGE (RAGE) protein expression significantly. Expressions of interleukin-6 (IL-6) and NF-kappa B p65 subunit were down-regulated significantly by flaxseed oil or fish oil diet. The histological tubular injuries were also lowered by both diets. These results suggest that dietary omega-3 fatty acids may slow the progression of diabetic nephropathy (DN) associated with oxidative stress, glycation, and inflammation in the kidney.
Keywords: Diabetes; Fish oil; Flaxseed oil; Glycation; Kidney; Streptozotocin